Geochemistry of oceanic anoxic events - Jenkyns, H (2010)
Oceanic anoxic events (OAEs) record profound changes in the climatic and paleoceanographic state of the planet and represent major disturbances in the global carbon cycle. OAEs that manifestly caused major chemical change in the Mesozoic Ocean include those of the early Toarcian (Posidonienschiefer event, T-OAE, ∼183 Ma), early Aptian (Selli event, OAE 1a, ∼120 Ma), early Albian (Paquier event, OAE 1b, ∼111 Ma), and Cenomanian-Turonian (Bonarelli event, C/T OAE, OAE 2, ∼93 Ma). Currently available data suggest that the major forcing function behind OAEs was an abrupt rise in temperature, induced by rapid influx of CO2 into the atmosphere from volcanogenic and/or methanogenic sources. Global warming was accompanied by an accelerated hydrological cycle, increased continental weathering, enhanced nutrient discharge to oceans and lakes, intensified upwelling, and an increase in organic productivity. An increase in continental weathering is typically recorded by transient increases in the seawater values of 87Sr/86Sr and 187Os/188Os ratios acting against, in the case of the Cenomanian-Turonian and early Aptian OAEs, a longer-term trend to less radiogenic values. This latter trend indicates that hydrothermally and volcanically sourced nutrients may also have stimulated local increases in organic productivity. Increased flux of organic matter favored intense oxygen demand in the water column, as well as increased rates of marine and lacustrine carbon burial. Particularly in those restricted oceans and seaways where density stratification was favored by paleogeography and significant fluvial input, conditions could readily evolve from poorly oxygenated to anoxic and ultimately euxinic (i.e., sulfidic), this latter state being geochemically the most significant. The progressive evolution in redox conditions through phases of denitrification/ anammox, through to sulfate reduction accompanied by water column precipitation of pyrite framboids, resulted in fractionation of many isotope systems (e.g., N, S, Fe, Mo, and U) and mobilization and incorporation of certain trace elements into carbonates (Mn), sulfides, and organic matter. Sequestration of CO2 in organic-rich black shales and by reaction with silicate rocks exposed on continents would ultimately restore climatic equilibrium but at the expense of massive chemical change in the oceans and over time scales of tens to hundreds of thousands of years. Copyright 2010 by the American Geophysical Union.